Farm Ponds in Northern Dry Zone of Karnataka: Impacts and Constraints - Ravi Dupdal; S. L. Patil; B. S. Naik; M. N. Ramesha; K. N. Ravi (Indian Journal of Extension Education, 2022)
This study ascertained the impact of water harvesting structures-farm ponds constructed under Krishi Bhagya Scheme in Northern dry zone of Karnataka during 2019 to 2021. Farmers with and without farm ponds were selected through multi-stage random sampling technique with a total sample size of 320 farmers for data collection. The impact of farm ponds on cropping pattern and crop productivity was visible due to supplementary life saving irrigation. The change in income due to farm ponds ranged from 13 to 97 per cent and net returns realized by farmers with ponds was higher than the farmers without ponds due to increased crop yield. The employment generation per farm increased for beneficiary farmers as compared to control. However, problems of sedimentation, poor design of farm ponds (absence of silt trap and proper inlet and outlet), poor site selection and lack of awareness were the major constraints experienced by farmers for long term sustainability of farm ponds.